2020
DOI: 10.15376/biores.15.4.9166-9179
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on laccase activity of white rot fungi under submerged fermentation with different lignocellulosic wastes

Abstract: Different Pleurotus ostreatus and Flammulina velutipes species were compared relative to their ability to produce laccase in submerged fermentation of various lignocellulosic wastes. Fungi cultivation in identical culture conditions revealed wide differences among both species and strains of the same species. The laccase secretion ability of P. ostreatus strains was superior to F. velutipes strains. Maximum laccase production on cottonseed hull, corncob, and poplar wood was secreted by P. ostreatus CY 568, P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 43 publications
(69 reference statements)
1
35
0
Order By: Relevance
“…The optimal conditions for laccase production from T. versicolor were found at 35 • C and 5 g/L of wheat bran as substrate, reaching approximately 200 U/ml on 11 days in submerged fermentation (Atilano-Camino et al, 2020). An et al (2020b) reported that laccase production from P. ostreatus and Flammulina velutipes strains grown on cottonseed hull was better than that on corncob or poplar wood, and laccase production from P. ostreatus CCEF 89 grown on cottonseed hull, corncob, and poplar sawdust ranged from 61.38 ± 4.09 to 748.24 ± 9.53 U/L, 26.12 ± 2.28 to 699.12 ± 44.91 U/L, and 3.32 ± 0.30 to 509.75 ± 15.43 U/L, respectively. So, previous studies were mainly focused on the effect of single lignocellulosic biomass on laccase activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal conditions for laccase production from T. versicolor were found at 35 • C and 5 g/L of wheat bran as substrate, reaching approximately 200 U/ml on 11 days in submerged fermentation (Atilano-Camino et al, 2020). An et al (2020b) reported that laccase production from P. ostreatus and Flammulina velutipes strains grown on cottonseed hull was better than that on corncob or poplar wood, and laccase production from P. ostreatus CCEF 89 grown on cottonseed hull, corncob, and poplar sawdust ranged from 61.38 ± 4.09 to 748.24 ± 9.53 U/L, 26.12 ± 2.28 to 699.12 ± 44.91 U/L, and 3.32 ± 0.30 to 509.75 ± 15.43 U/L, respectively. So, previous studies were mainly focused on the effect of single lignocellulosic biomass on laccase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the biosynthetic potential of Basidiomycetes was highly dependent on the species of fungi (Han et al, 2021a). An et al (2020b) reported that the capacity of secreting laccase of P. ostreatus strains was superior to F. velutipes strains due to the maximum laccase production on cottonseed hull, corncob, and poplar wood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the difference of laccase activity on different lignocellulosic biomass by fungi, it is important to study the laccase activity among different agricultural and forestry residues. Previous studies on Pleurotus ostreatus and Ganoderma lingzhi focused on laccase production induced by metals, temperature, and grown on two or three substrates (Elissetche et al 2007;Postemsky et al 2017;An et al 2020b;Han et al 2020b). Hence, this paper presents evaluation of laccase production by P. ostreatus CY 568 and G. lucidum Han 500 in various agricultural and forestry residues.…”
Section: Production Of Laccase Under Different Agricultural and Forestry Residuesmentioning
confidence: 99%
“…Moreover, type of fungal species or strains is an important factor affecting laccase production. Laccase activity of different strains from the genera, Pleurotus and Flammulina on substrate of wood, tree leaves, corncob, and wheat straw have been investigated (An et al 2020b;Han et al 2017Han et al , 2020b. Laccase production of Ganoderma lucidum has been discussed in the effect of rice and sunflower agro-residues, phenolic, and metallic inducers (Kuhar and Papinutti 2014;You et al 2014;Postemsky et al 2017;Palazzolo et al 2019).…”
Section: Introductionmentioning
confidence: 99%